Activation of ice recrystallization inhibition activity of poly(vinyl alcohol) using a supramolecular trigger. Issue 9 (4th February 2016) - Phillips, Daniel J.; Congdon, Thomas R.; Gibson, Matthew I.
Abstract : External control over the antifreeze protein mimetic activity of poly(vinyl alcohol) is enabled by Fe 3+ driven supramolecular assembly. Abstract : Antifreeze (glyco)proteins (AF(G)Ps) have potent ice recrystallisation inhibition (IRI) activity – a desirable phenomenon in applications such as cryopreservation, frozen food and more. In Nature AF(G)P activity is regulated by protein expression levels in response to an environmental stimulus; temperature. However, this level of regulation is not possible in synthetic systems. Here, a synthetic macromolecular mimic is introduced, using supramolecular assembly to regulate activity. Catechol-terminated poly(vinyl alcohol) was synthesised by RAFT polymerization. Upon addition of Fe 3+, larger supramolecular star polymers form by assembly with two or three catechols. This increase in molecular weight effectively 'switches on' the IRI activity and is the first example of external control over the function of AFP mimetics. This provides a simple but elegant solution to the challenge of external control of AFP-mimetic function.